Association of socioeconomic, school-related and family factors and physical activity and sedentary behaviour among adolescents: multilevel analysis of the PRALIMAP trial inclusion data - Johanne Langlois; Abdou Y Omorou; Anne Vuillemin; Serge Briançon; Edith Lecomte; PRALIMAP Trial Group (BMC, 2017)
Abstract Background Social differences among adolescents in physical activity and sedentary behaviour have been identified but are not well explained. The current study aimed to identify socioeconomic, family and school-related associated factors with physical activity and sedentary behaviour among high-school adolescents. Methods This was a cross-sectional analysis of T0 physical activity and sedentary behaviour of 2523 students 14 - 18 years old recruited for the PRALIMAP trial from 24 French state-run high schools. Data were collected by self-administered questionnaire at the start of grade 10. Adolescents completed the International Physical Activity Questionnaire for physical activity and sedentary behaviour and an ad hoc questionnaire for active commuting and sport participation. Statistical analyses involved linear and logistic regressions. Results Socioeconomic, family or school variables were associated with levels of physical activity and sedentary behaviour for both boys and girls, but no factor, except perceived parental physical activity level, was associated with total energy expenditure (total physical activity) for either gender. Adolescents with privileged and less privileged socioeconomic status reported the same total amount of energy expenditure. Conclusions Total physical activity score alone is not sufficient to assess the physical activity of adolescents. These findings may have implications for better understanding of social inequalities in this context and recommendations to prevent overweight. Trial registration This trial is registered at ClinicalTrials.gov ( NCT00814554 ). The date of registration: 23 December 2008. Registration was not required at the time of the start of PRALIMAP for public health and prevention programmes and trials.